Geodetic monitoring of landslide processes in coastal territories - Bulysheva, Daria; Leonidova, Iryna; Malashchuk, Oksana; Movchan, Tetiana; Varfolomeyeva, Oksana; Panasuk, Olga (Geodesy and Cartography, 2025)
The study is devoted to the methodology and features of geodetic monitoring of territories to provide analytical and predictive information regarding predicting the danger of coastal strip landslide processes. The causes, consequences, and risks of the development of landslide processes are analysed. The purpose of the study was to justify the need and to consider the methodology of stable high-precision observations of the coastal fortification structure, to identify the zone of active landslides, and to provide suggestions regarding the features and conditions of further observations. To conduct direct observations, it was necessary to lay benchmarks on the territory of the research object. The method using GNSS technologies was chosen for determining the coordinates of benchmarks at the research object. The advantages of using GNSS equipment for monitoring slope deformations compared to traditional geodetic methods have been determined. To achieve the maximum accuracy of measurements, it was decided to install a constantly operating satellite station of the “System.NET” network directly in the work area. During the study period, 33 geodetic soil benchmarks and 53 benchmarks were installed on the coastal fortification structure in the coastal zone. In combination with the methods of geodetic observations, such a density and distribution of benchmarks both in the soil and on the coastal fortification structure made it possible to obtain accurate data on the dynamics of landslide processes and to prevent the negative consequences of the landslide.